26.0k views
2 votes
(2x + 3y) + (4x - 3y) = 11+(-5)

Which of the following is equivalent to the equation above?
A. 6x=10
B. 6x=16
C. 6x+6y=6
D. 6x+6y=16

1 Answer

6 votes

Answer:

The correct option should have been
6x=6.

Explanation:

Given the expression


\left(2x\:+\:3y\right)\:+\:\left(4x\:-\:3y\right)\:=\:11+\left(-5\right)

solving the expression


\left(2x\:+\:3y\right)\:+\:\left(4x\:-\:3y\right)\:=\:11+\left(-5\right)

Remove parentheses: (a) = a


2x+3y+4x-3y=11-5

Group like terms


3y-3y+2x+4x=11-5

Add similar elements


6x=6

It is clear that not a single given option is
6x=6. It means no option is correct. It seems you mistyped the correct options.

The correct option should have been
6x=6.

User JR White
by
5.3k points